Association between the built environment and active transportation among U.S. adolescents. (December 2019) - Tewahade, Selam; Li, Kaigang; Goldstein, Risë B.; Haynie, Denise; Iannotti, Ronald J.; Simons-Morton, Bruce
Abstract: Introduction: As a major determinant of obesity and cardiovascular disease in the United States, decreasing physical activity (PA) has led researchers to study factors influencing daily PA. One opportunity for modifying PA is in relation to transportation to and from school and/or work. We examined the association between characteristics of the built environment of home neighborhoods and transportation-related PA to school or work among youth and emerging adults. Methods: The data were drawn from Waves 1 and 4 of the NEXT Generation Health Study (n = 2780), a nationally representative, longitudinal cohort study starting with 10th grade (Wave 1) in the 2009–2010 school year. Modes of travel to/from school were categorized into three groups: those using active transportation (walking/cycling), public transportation, and passive transportation (being driven or chauffeured/driving). Neighborhood characteristics included land use mix, street connectivity, residence density, park density, recreational density, and walkability. Multinomial logistic regressions and one-way ANOVAs were used to examine multivariate associations between modes of travel to and from work/school and neighborhood characteristics. Analysis accounted for complex survey features including stratification, clustering and sampling weights. Results: After controlling for covariates (i.e., ethnicity, sex, education, and socioeconomic status), more land use diversity, street connectivity, residence density, and walkability were significantly correlated with active transportation in both waves and more park and recreational density were significantly correlated with active transportation in Wave 1, compared with passive transportation. Conclusions: More mixed land use, greater connected streets as well as higher walkability and density of residence, parks and recreational facilities were associated with active transportation; suggesting city planning officials may consider creating more walkable and liveable communities to promote daily transportation-related PA. Highlights: The built environment was correlated with daily commuting behavior in youth. Land use and street connectivity were associated with active transportation. Public transportation use was positively correlated with the built environment in adolescents.